1993
DOI: 10.1016/0735-1097(93)90360-d
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in aortic growth explain aortic arch gradients during exercise

Abstract: Exercise testing detects hypertension and arch gradients in patients with a good coarctation repair as assessed at rest. The hypertension and arch "obstruction" appear to be related to discrepancies in the growth of the transverse aortic arch proximal to the repair site, rather than a "recoarctation" of the aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 12 publications
0
30
1
Order By: Relevance
“…This is probably because the blood pressure difference is influenced by factors such as altered arterial reactivity and baroreceptor function in the pre-coarctation vascular bed, which lead to increased blood pressure variability (Gardiner et al 1994;Guenthard and Wyler 1995). Some studies have also reported an increased arterial stiffness in the pre-coarctation vascular bed (Gardiner et al 1994;Ong et al 1992), aortic arch gradient due to discrepancies in growth of the transverse aortic arch (Weber et al 1993), hypoplasia of the distal aortic arch (Bharati and Lev 1986) and a hyperdynamic left ventricle (Ong et al 1992;Leandro et al 1992). Increased levels of catecholamines in the blood and changes in the renin-angiotensin system (Alpert et al 1979;Parker et al 1980Parker et al , 1982, and enhanced sympathetic nerve activity have been reported.…”
Section: Discussionmentioning
confidence: 94%
“…This is probably because the blood pressure difference is influenced by factors such as altered arterial reactivity and baroreceptor function in the pre-coarctation vascular bed, which lead to increased blood pressure variability (Gardiner et al 1994;Guenthard and Wyler 1995). Some studies have also reported an increased arterial stiffness in the pre-coarctation vascular bed (Gardiner et al 1994;Ong et al 1992), aortic arch gradient due to discrepancies in growth of the transverse aortic arch (Weber et al 1993), hypoplasia of the distal aortic arch (Bharati and Lev 1986) and a hyperdynamic left ventricle (Ong et al 1992;Leandro et al 1992). Increased levels of catecholamines in the blood and changes in the renin-angiotensin system (Alpert et al 1979;Parker et al 1980Parker et al , 1982, and enhanced sympathetic nerve activity have been reported.…”
Section: Discussionmentioning
confidence: 94%
“…Several authors recommended exercise testing in the post-operative assessment of patients after repair of AoC for the detection of residual aortic gradients [19][20][21]. In contrast, others did not find a significant residual aortic arch gradient that could explain the post-operative exercise-induced hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…The basis for a persistent hypoplasia of the TAA is unknown. End-to-end anastomosis does not enlarge the small horizontal aorta proximal to the AoC, but also discrepancies in the growth of the aortic arch proximal to the repair site have been suggested [19].…”
Section: Discussionmentioning
confidence: 98%
“…Weber and associates [43], utilizing maximal treadmill tests and isoproterenol infusion during cardiac catheterization, demonstrated aortic arch gradients in postop CoA patients who had no significant gradients or narrowing at the site of repair. They concluded that in some cases, discrepancies in growth of the transverse aortic arch (proximal to the coarct repair) may cause arch gradients and hypertension with exercise.…”
Section: Exercise Testing In Postoperative Coarctation Of the Aorta Pmentioning
confidence: 98%